Teriparatide treatment complicated by malignant myeloma. (16th August 2010) - Koski, Anna-Mari; Sikiö, Anu; Forslund, Terje
Abstract : Recombinant human parathyroid hormone (1–34) (rhPTH 1–34), teriparatide (Forsteo in Europe), is a new compound that has been introduced and shown to be successful in the treatment of osteoporosis. The mechanisms of action include a pulsative influence on the RANKL/OPG system resulting in osteoblast activation and increased bone formation by teriparatide. In malignant myeloma there is an imbalance between osteoclast and osteoblast activity with involvement of the RANKL/OPG system among others. We report a case with monoclonal gammopathy of uncertain significance (MGUS) who developed malignant myeloma after teriparatide treatment and we suggest that in addition to malignant myeloma and smouldering myeloma, MGUS should also be considered contraindicated for teriparatide treatment.